Comparative evaluation between diameter difference of thumb and asymmetry of lateral cerebral ventricles in child with developmental delay; a new finding - KEIHANI DOUST, Zarintaj; SHARIAT, Mamak; RAHIMIAN, Elham; TEHRANI, Fatemeh; SADDIGHI, Gholamreza (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Keihanidoust Z, Shariat M, Rahimian E, Tehrani F, Saddighi Gh. Comparative Evaluation between Diameter Difference of the Thumb and Asymmetry of Lateral Cerebral Ventricles in Children with Developmental Delay: A New Finding. Iran J Child Neurol. Summer 2015;9(3):9-12. Abstract Objective Anthropometry (measurement of body dimensions) has been used for clinical diagnosis of growth and developmental disorders during pregnancy and after birth. Different brain volumes have also been shown in abnormal developmental disorders. This study compares the different horizontal diameters of the left- and right-hand thumbnails and asymmetry of lateral cerebral ventricles in children with developmental delays. Materials & Methods This retrospective case control study was carried out in the Pediatric Neurologic Outpatient of a university hospital in Tehran, Iran (2009–2011). Twenty-eight patients with motor developmental disorders (case) and 28 healthy individuals (control) had brain MRIs and volume of lateral cerebral ventricles size had been studied. The maximum horizontal diameters of the left and right thumbnails were measured by calipers during physical and neurological exams by a pediatric neurologist. Finally, we compared and analyzed different horizontal diameters of the left and right hand thumbnails and asymmetry of lateral cerebral ventricles. Results There was a significant correlation between asymmetry of brain lateral ventricles size and mean difference of horizontal diameter of thumb nails (P = 0.0001). A meaningful relation between brain hemispheres asymmetry and developmental delay (P = 0.04) was seen. Conclusion The asymmetry of thumbnails can be a marker for asymmetry of lateral ventricles and child developmental delays.